Increase Women Leaders As a Corporate Performance Drivers In Building Material Company - Izzati, Nailu Nur; Bangun, Madju Yuni Ros (Jurnal Bisnis dan Keuangan, 2023)
SDG 5, or Sustainable Development Goal 5, is one of the 17 goals established by the United Nations in 2015 as part of the 2030 Agenda for Sustainable Development. SDG 5 grants women and girls equal rights and opportunities to live free without discrimination, including workplace discrimination, career opportunities, and violence. The achievement of SDG 5 is critical to creating a sustainable future where women can contribute to society without fear of discrimination. The problem statement in this research is what key success, motivation, and competency are needed for women to become leaders, there are a constraint and perceptions about women that can be barriers to becoming a leader, how support system can help women to become leaders, women have limitations in their career development. The dependent variable in this study is the "Leadership" driver and the independent variables in this study are the "General/Key Success", "Motivation", "Ability", "Role", "Situational" and "Constraint" drivers. Situational Factors, constraints, general/key success and abilities significantly influence women's leaders. To increase women's leadership at SIG, the things that need to be improved are: create a women's leadership program at the age of 30s by increasing the competencies that are important for women to improve, provide facilities for women employees, so that their obstacles can be minimized, such as daycare, breastfeeding rooms, etc., increase women's confidence to show their abilities, increasing women's motivation in self-actualization, improving the support system for women from family